2012
DOI: 10.1037/a0025988
|View full text |Cite
|
Sign up to set email alerts
|

Switching on and switching off in mathematics: An ecological study of future intent and disengagement among middle school students.

Abstract: Prompted by international concerns about school and postschool participation in mathematics, the authors of the present study sought to investigate factors predicting "switching on" and "switching off in mathematics, operationalized through measures of future intent and disengagement, respectively. They drew from Bronfenbrenner's ecological model to explore an educational ecology comprising student, home, classroom, school, and time factors in predicting future intent and disengagement. These models were condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
98
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(102 citation statements)
references
References 98 publications
4
98
0
Order By: Relevance
“…Student enjoyment of mathematics is also recognised as a key ingredient for addressing student disengagement (A.J. Martin et al, 2012) and, given that attitudes towards mathematics are not stable and fixed (Pierce, Stacey, & Barkatas, 2007), innovative interventions, such as PA integration, have the potential to positively affect attitudes and engagement (Pierce et al, 2007). The NSW Auditor General"s report (2012) (Department for Education and communities, 2012) highlighted, as one of its recommendations, the need to improve children"s physical activity levels through the integration of physical activity within the existing curriculum.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Student enjoyment of mathematics is also recognised as a key ingredient for addressing student disengagement (A.J. Martin et al, 2012) and, given that attitudes towards mathematics are not stable and fixed (Pierce, Stacey, & Barkatas, 2007), innovative interventions, such as PA integration, have the potential to positively affect attitudes and engagement (Pierce et al, 2007). The NSW Auditor General"s report (2012) (Department for Education and communities, 2012) highlighted, as one of its recommendations, the need to improve children"s physical activity levels through the integration of physical activity within the existing curriculum.…”
Section: Resultsmentioning
confidence: 99%
“…Mathematical enjoyment is considered particularly significant for addressing student disengagement (A.J. Martin et al, 2012). However, researchers have found that mathematics classrooms and the individualistic nature of mathematics, whereby students work independently, actually discourages both social interaction and learning, which could reduce engagement and understanding (Attard, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supportive teacher-student interactions promote student engagement and learning and have appreciable effect on learning outcomes [43,44]. Nevertheless, with the increasing number of large classes in universities, the opportunity of discourse between teachers and students has abated.…”
Section: B Promoting Teacher-student Interactionmentioning
confidence: 99%
“…Self-efficacy expectations (SEE) are related to key learning behaviours and outcomes such as individuals' motivation and engagement (Martin et al 2012), goal setting behaviours (Bong 2009), persistence (Multon et al 1991), and physiological experiences (Meece et al 1990). In mathematics in particular, SEE have been linked with perseverance (Zeldin and Pajares 2000), performance outcomes (Schulz 2005), attitudes towards mathematics and choice of maths-related courses and careers (Hackett and Betz 1989).…”
Section: Introductionmentioning
confidence: 99%